Description of the Science Learning Process for Grade III Elementary School Students - Septian Zuhri Kuncoro; Imaniar Purbasari; Sekar Dwi Ardianti (JURNAL PENDIDIKAN IPS, 2025)
The implementation of IPAS learning in elementary schools still faces challenges, particularly in applying a systematic scientific process and fostering active student engagement. IPAS learning is designed to help students understand the environment through an integrated approach that combines natural and social sciences. This study aims to examine the learning process and learning outcomes of IPAS learning among third-grade students at SD 4 Loram Kulon. IPAS learning is structured to equip students with scientific understanding through stages such as observation, question formulation, investigation, data analysis, evaluation, and presentation of findings. This process aims to develop students’ scientific process skills in a systematic and continuous manner. This qualitative study employed a narrative approach and involved 14 students as research subjects. Data were collected through observation, interviews, and documentation during the learning activities and analyzed descriptively. The findings reveal that the IPAS learning process in third grade at SD 4 Loram Kulon has comprehensively addressed the stages of skills and understanding, promoting active student participation. Furthermore, student learning outcomes showed improvement in verbal information, intellectual skills, cognitive strategies, attitudes, and motor skills. These results suggest that IPAS learning contributes positively to the development of students' scientific thinking and overall learning experience.